A aplicação da teoria dos precedentes judiciais no processo do trabalho - Amaral, Felipe Marinho (2020)
In order to analyze the theory of judicial precedents and their application in the labor process, the present study aimed, initially, to trace historical aspects of the civil law and common law traditions, within the context of judicial precedents. It is true that the theme, since it has been studied historically predominantly within the common law tradition it needed to deal with historical aspects, including, to demonstrate that the rigid division between traditions can no longer be done. Starting from this idea, it cannot be denied that the theoretical and practicaljurisprudential development occurred primarily in countries such as, for example, England and the United States of America. In this way, and for that reason, the theoretical bases of the theory were developed mainly in these countries. Therefore, the work analyzed the bases of the precedent theory, addressing concepts, techniques and procedures necessary for the application of the theory. The other side, with the objective of demonstrating the existence of institutes, procedures and techniques in the Brazilian legal system, traditionally aligned with civil law, the historical foreshortening through instruments that were and still are part of the Brazilian system related to the importance of judicial decisions is imperative and its mandatory application. Undoubtedly, the Federal Constitution is the interpretative and validity vector of the entire internal system, therefore, it is necessary to submit the theory to the constitutional text, in order to verify its applicability and effectiveness of the constitutional principles and guarantees. It cannot be forgotten, either, that the Code of Procedure 2015 inaugurated a microsystem for the application of judicial precedents, which had been analyzed, including in relation to possible arguments that, for part of the doctrine, would make the microsystem unconstitutional. After ruling out possible arguments in favor of unconstitutionality, the present study inserted the discussions within the context of the labor process, demonstrating that there is no incompatibility in its application, so that it is necessary to apply the theory of judicial precedents in the labor process. In this line, the classifications and types of judicial precedents applicable to the labor process were analyzed, as well as the summaries, jurisprudential guidelines and prevailing theses. Furthermore, the importance of applying the theory is not restricted to the performance of the courts, and, therefore, the relevance of the first degree of jurisdiction in this context has been demonstrated. Thus, the objective was to bring the discussion of the theory of judicial precedents to the labor process, positioning itself by its application, provided that certain basic principles and peculiarities of the labor process are respected